Preparation and morphology-dependent wettability of porous alumina membranes - Shimanovich, Dmitry L.; Vorobjova, Alla I.; Tishkevich, Daria I.; Trukhanov, Alex V.; Zdorovets, Maxim V.; Kozlovskiy, Artem L. (Beilstein Journal of Nanotechnology, 2018)
This article presents the preparation and study of the wetting properties of porous alumina membranes (PAMs) with a thickness of 25 to 75 μm and with a different pore sizes. The fabrication process features, scanning electron microscopy and atomic force microscopy characterization results are presented. The comparative analysis of PAM surfaces (outer and inner) and the effect of morphology of these surfaces on the wetting properties are discussed. Both alumina surfaces show significant morphology-dependent wettability. Measurements of the interfacial contact angle were made on the as-fabricated amorphous membrane and after pore widening with a range of pore diameters from 25 to 100 nm. The possible applications of PAMs for various membrane technologies is shown.
Keywords: interfacial contact angle; membranes; porous anodic alumina; wettability